TEACHING WRITING A NARRATIVE PARAGRAPH BY USING NOTE-TAKING TECHNIQUE - Eni Kusnita (Universitas PGRI Palembang, 2019)
Abstract: The main problem of this research was â€œis it effective to teach narrative paragraph in writing by using Note-taking technique to the eighth grade students of the state junior high School 33 of Palembang?â€. Therefore, the objective of this research was to find out whether or not it was effective to teach writing narrative paragraph by using Note-taking technique to the eighth grade students of the state Junior High school 33 of Palembang. Â The method used in this research was pre-experimental method that is one group pre-test post-test method. The population of this research was all of the eighth grade students of the state Junior High school 33 of Palembang. The sample of this research consisted of 37 students. In this research there were two variables, they were independent variable and dependent variable. The independent variable of this research was note-taking and dependent variable was the studentsâ€™ writing achievement. In collecting the data, the written test was giving twice; pre-test and post-test. The data were analyzed by using matched t-test. Â Based on the result of the data analysis, the result of the research showed that the studentsâ€™ average score in the pretest was 63.58 in which the lowest score was 50 attained by two students and the highest score was 70 reached by two students. Then the studentsâ€™ average score in the posttest was 72.08 where the lowest score 60 achieved by one student and the highest score was 80 achieved by five students. By using the studentsâ€™ score it was found that the result of the calculation of the matched t-test was 8.854, this score was higher than t-table that was 1.684 and the critical value at 5% of the significant level in one-tailed testing with df= 36. It means that null hyporesearch (Ho) was rejected and alternative hyporesearch (Ha) was accepted since the result of t-obtained was higher that t-table. In other words, the teaching writing narrative paragraph by using note-taking technique to the eighth grade students of the state Junior high School 33 of Palembang was effective.